The first case report of Haim Munk disease with neurological manifestations and literature review - Mehdi Moghaddasi (Clinical Case Reports, 2021)
Abstract HMS can have neurologic MS like manifestations. It is urgent to do more research and report probable unknown associations of HMS for its better management.